2012
DOI: 10.2174/1875413901205010073
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Dust Aerosols Impact on Hurricanes with Multi-Sensors Measurement from Space

Abstract: MODerate resolution Imaging Spectroradiometer (MODIS) Aerosol Optical Thickness (AOT) and the Atmospheric Infrared Sounder (AIRS) atmospheric profiles (temperature and moisture) Level 2 products are studied to investigate dust aerosols impacts on hurricanes through spatial analysis. Spatial regions were selected based on two concentric circles (an annulus) and segmented by left and right regions of 180° each around the hurricanes center. Statistical relationships between MODIS AOT, AIRS temperature and percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…As a consequence, to this shift, weak storm systems were formed and this further caused suppression or delay in formation of storm systems. Similar observations were reported by Kamal, M., et al, [21] who showed that presence of dust in hurricane systems tended to reduce the energy of the developing system. Hence, the out of phase and lower amount of dust transport caused the incubation period to about 192 days before the 1 st Atlantic storm was observed.…”
Section: Resultssupporting
confidence: 89%
“…As a consequence, to this shift, weak storm systems were formed and this further caused suppression or delay in formation of storm systems. Similar observations were reported by Kamal, M., et al, [21] who showed that presence of dust in hurricane systems tended to reduce the energy of the developing system. Hence, the out of phase and lower amount of dust transport caused the incubation period to about 192 days before the 1 st Atlantic storm was observed.…”
Section: Resultssupporting
confidence: 89%
“…Based on the wind speed, pressure and humidity received by the airplane, forecasters can explain whether the hurricane is weakening or intensifying. Factors such as vertical wind shear [2][3][4][5], atmospheric moisture [6,7], air temperature [6], sea surface temperature [8,9] and dust aerosols [6,7,10] may also impact the intensity [11,12] of the hurricane after it has formed. To sustain a strong hurricane, water temperature above 80°F and warm water depths of 150 feet are needed while strong vertical shear in the atmospheric horizontal winds around the hurricane dampen its force [1].…”
Section: Introductionmentioning
confidence: 99%
“…To sustain a strong hurricane, water temperature above 80°F and warm water depths of 150 feet are needed while strong vertical shear in the atmospheric horizontal winds around the hurricane dampen its force [1]. Extremely dry conditions in the mid-atmosphere may act as an agent of taming hurricane force as well [6,10]. Also, Houze et al [13] reported the dynamics of the internal structure of the vortex are responsible for hurricane intensity changes, and they suggested improvements on physical understanding in forecasting hurricane intensity modeling of the internal structure of the vortex.…”
Section: Introductionmentioning
confidence: 99%